Fuzzy logic approach for analysis and simulation of human motion - Karaköse, Mehmet (My University, 2010)
Analysis and simulation of human motion is an important issue for many industrial applications and developing of humanoid robots. Dynamic model of everyday life movements such as walking, running, jumping, lifting, and various sports is useful for biomechanical analysis of human. In this study, analysis of lifting motion based on two dimensional and five segment human model has been performed using a fuzzy system. The Matlab simulations have been given to presenting effectiveness of proposed approach. The simulation results shows accuracy of expected movements from human model consist of elbow, shoulder, hip, knee, and ankle.
İnsan hareketlerinin analiz ve simülasyonu için bulanik mantik yaklaşimi
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: Anthropomorphic robots; Biomechanics; Computer simulation; Electrical engineering; Fuzzy sets; Industrial applications; Analysis and simulation; Biomechanical analysis; Fuzzy logic approach; Human Model; Human motions; Humanoid robot; Matlab simulations; Simulation result; Fuzzy logic